Kantovi argumenti za tezo »bit ni realni predikat« - Kravanja, Aljoša (Analiza: časopis za kritično misel, 2025)
Kant’s Grounds for the “Being is Not a Real Predicate” ThesisInfluentially, Kant argued against the ontological proof by suggesting that being is not a real predicate. He developed the thesis in the Only Possible Argument and later in Critique of Pure Reason. But what are the reasons Kant gave for the thesis on being? The paper claims that there are four separate arguments embedded in Kant’s text: the descriptive argument, the argument from the thoroughly determined concept, the argument from comparison, and the identification argument. The respective advantages and sometimes surprisingly trivial flaws of the arguments are examined. The paper argues that the fourth argument appears to be the strongest one, even though the classic treatments of Kant’s thesis (Hegel, Heidegger, Barnes, Hintikka) concentrate on the first three.
Keywords: Kant; existence; being; predicate; property